The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/rs9060610
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plot Size on Efficiency of Biomass Estimates in Inventories of Dry Tropical Forests Assisted by Photogrammetric Data from an Unmanned Aircraft System

Abstract: Abstract:Applications of unmanned aircraft systems (UASs) to assist in forest inventories have provided promising results in biomass estimation for different forest types. Recent studies demonstrating use of different types of remotely sensed data to assist in biomass estimation have shown that accuracy and precision of estimates are influenced by the size of field sample plots used to obtain reference values for biomass. The objective of this case study was to assess the influence of sample plot size on effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 57 publications
(77 reference statements)
5
34
0
1
Order By: Relevance
“…These findings concur with previous studies in both temperate [20,21,38] and tropical forests [39,40] highlighting the importance of selecting an appropriate plot size for forest inventories used for estimating forest biomass. Studies in tropical dry forests in Malawi using photogrammetric data showed the same trend of increasing accuracy with increasing sample plot size [41].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…These findings concur with previous studies in both temperate [20,21,38] and tropical forests [39,40] highlighting the importance of selecting an appropriate plot size for forest inventories used for estimating forest biomass. Studies in tropical dry forests in Malawi using photogrammetric data showed the same trend of increasing accuracy with increasing sample plot size [41].…”
Section: Discussionmentioning
confidence: 69%
“…Thus, the R 2 values of cross validations increased by 0.25 (a 76% increase) from 80 m 2 (0.33) to 400 m 2 (0.58) but only by 0.17 (a 29% increase) from 400 m 2 to 1000 m 2 (0.75) in Kiuic, and by 0.28 (a 120% increase) from 80 m 2 (0.23) to 400 m 2 (0.51) but only by 0.16 (a 31% increase) from 400 m 2 to 1000 m 2 (0.67) in FCP. These results are relevant because, as plot sizes increases, the cost of field sampling also increases [41]. Therefore, the selection of an optimal plot size for AGB estimation from LiDAR data should take into account a trade-off between estimation accuracy and plot establishment cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precision and accuracy of AGB extrapolated from field plot data are affected by the size and shape of the plots [64]. Most of the used field plots in the present study exceed an area of 1000 m 2 , a size large enough to be more robust against boundary effects and less sensitive to individual trees [65][66][67]. Aside from the size, the shape affects the results of extrapolated AGB.…”
Section: Validation Datasetsmentioning
confidence: 92%
“…Nevertheless, the low cost and increased repeatability of DAP relative to ALS, for stand-level applications, shows significant potential [27,29]. Recent studies indicate that accurate DEM generation from the unsupervised classification of DAP point clouds under open forest canopies is achievable [29,31,46,47]. For example Guerra-Hernández et al [31] used 20 high precision GPS checkpoints and found RMSE of 0.046 m, 0.018 m and 0.033 m in the X, Y and Z directions respectively.…”
Section: Introductionmentioning
confidence: 99%